Caitanya Vaisnava Philosophy: Tradition, Reason and Devotion, edited by Ravi M. Gupta - Venkatesan, Archana (Religions of South Asia, 2018)
Caitanya Vaisnava Philosophy: Tradition, Reason and Devotion, edited by Ravi M. Gupta. Dorchester, UK: Ashgate, 2014. viii + 244 pp., 153.00 (hb), 54.95 (pb). ISBN 978-0754661771 (hb), 978-1-138-24885-4 (pb).